Evidence for CP violation in B+ → pp̄K+ decays - Aaij, Roel; Bachmann, Sebastian; Bien, Alexander; Comerma-Montells, Albert; De Cian, Michel; Dordei, Francesca; Esen, Sevda; Färber, Christian; Gersabeck, Evelina; Grillo, Lucia; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Physical review letters, 2014)
Three-body B+→p¯pK+ and B+→p¯pπ+ decays are studied using a data sample corresponding to an integrated luminosity of 3.0 fb−1 collected by the LHCb experiment in proton-proton collisions at center-of-mass energies of 7 and 8 TeV. Evidence of CP violation in the B+→p¯pK+ decay is found in regions of the phase space, representing the first measurement of this kind for a final state containing baryons. Measurements of the forward-backward asymmetry of the light meson in the p¯p rest frame yield AFB(p¯pK+,mp¯p<2.85 GeV/c2)=0.495±0.012 (stat)±0.007 (syst) and AFB(p¯pπ+,mp¯p<2.85 GeV/c2)=−0.409±0.033 (stat)±0.006 (syst). In addition, the branching fraction of the decay B+→¯Λ(1520)p is measured to be B(B+→¯Λ(1520)p)=(3.15±0.48 (stat)±0.07 (syst)±0.26 (BF))×10−7, where BF denotes the uncertainty on secondary branching fractions.